The effect of environmental conditions and agricultural media on the phenolic and chlorophyll content of the fern Asplenium ceterach L. - طراف رشا; وفاء رجب; حسن علاء الدين (Latakia University Journal -Biological Sciences Series, 2023)
This research aimed to study the effect of different agricultural media (Sand-Compost-Turb-Zeolite) and different environmental conditions (Lighting- Ventilation) by adding different concentrations of nutrient solutions on the Total phenolic and chlorophyll content of the fern Asplenium ceterach L.. The plant was collected. from several villages in the countryside of Qardaha in Lattakia city in February 2022 and the plant was cultivated in laborator. The concentration of total phenols, chlorophyll a and chlorophyll b was measured by using a spectrophotometer, and the statistical analysis (Anova test) was done using Costat program. The results showed that sand agricultural media was superior, followed by zeolite, turb and compost in terms of its effect on the decreased of Total phenolic concentration and increased Chlorophyll concentration of the cultivated plant. Concentrations of ideal nutrient solutions increased the Total phenolic and Chlorophyll concentration in the plant. There was no significant effect of each of the ventilation and lighting factors on the Total phenolic and Chlorophyll content in the studied plant.